1995
DOI: 10.21273/jashs.120.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Parent Effect on the Selective Abscission of `Mauritius' and `Floridian' Lychee Fruitlets

Abstract: Fruit produced by adjacent blocks of `Mauritius' and `Floridian' lychee (Litchi chinensis Sonn.) were sampled at four different stages of development and the embryos were analyzed for pollen parentage by phosphoglucose isomerase (PGI; EC 5.3.1.9) isozyme system. Hybrid percentage increased significantly from ≈5 weeks after fruit set to maturity as follows: from 29.5% to 76.3% in `Mauritius' and from 74.2% to 92.5% in `Floridian'. These findings clearly indicate selective absc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 8 publications
(2 reference statements)
8
27
0
Order By: Relevance
“…Many years ago, Swingle (1928) proposed that hormones produced by the seeds are responsible for the changes. Pollinizer effects on some traits were previously demonstrated in almond (Garc ıa-Gusano et al 2005;Gonz alez et al 2005;Sanchez-Perez et al 2012), apple (Ruth & Williams 1983;T oth et al 2005;Bodor et al 2008), blueberry (Gupton 1997;da Silveira et al 2011), chestnut (McKay & Crane 1939, cucumber (Olfati et al 2010), date palm (Swingle 1928;Muhtaseb & Ghanim 2006), grapefruit (Burger 1985), guava (Usman et al 2013), litchi (Degani et al 1995), loquat (Xu et al 2007), pear (Tufts & Hansen 1933;Nyeki 1972), pistachio (Crane & Iwakiri 1980), pecan (Marquard 1988), olive (Farinelli et al 2012), sour cherry (Ansari et al 2010), walnut (Golzari et al 2010) and watermelon (Freeman et al 2007).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many years ago, Swingle (1928) proposed that hormones produced by the seeds are responsible for the changes. Pollinizer effects on some traits were previously demonstrated in almond (Garc ıa-Gusano et al 2005;Gonz alez et al 2005;Sanchez-Perez et al 2012), apple (Ruth & Williams 1983;T oth et al 2005;Bodor et al 2008), blueberry (Gupton 1997;da Silveira et al 2011), chestnut (McKay & Crane 1939, cucumber (Olfati et al 2010), date palm (Swingle 1928;Muhtaseb & Ghanim 2006), grapefruit (Burger 1985), guava (Usman et al 2013), litchi (Degani et al 1995), loquat (Xu et al 2007), pear (Tufts & Hansen 1933;Nyeki 1972), pistachio (Crane & Iwakiri 1980), pecan (Marquard 1988), olive (Farinelli et al 2012), sour cherry (Ansari et al 2010), walnut (Golzari et al 2010) and watermelon (Freeman et al 2007).…”
Section: Introductionmentioning
confidence: 95%
“…They further indicated that there was a profound reduction in seed set due to self-pollination in a few cultivars having pistillate flowers. Degani et al (1995) showed that seed weights of litchi were affected by the pollen parent and that outcrossed fruits were heavier and contained heavier seeds than selfed ones. In contrast, Sabir (2011), using European (V. vinifera L.) and American rootstock species (Vitis spp.…”
Section: Seed Features (Xenia)mentioning
confidence: 99%
“…Lychee flowers are functionally unisexual and the overlap between male and female flowers is only partial within a cultivar (Stern and Gazit 1996). However, a higher survival of hybrid versus selfed fruits has been reported (Degani et al 1995b). Most of the cultivars analyzed in this study are ancient, and only some of them are selections obtained after open-pollination (Menzel and Simpson 1991).…”
Section: Ssr Polymorphism and Cultivar Identificationmentioning
confidence: 99%
“…However, when 'Mauritius' fruitlets weigh ca. 2 g, the late flowering 'Floridian' (Stern et ai., 1993;Degani et at., 1995a;Stern and Gazit, 1996) has 7-10 d younger fruitlets weighing about 1 g. Taking into account the advantage of being able to spray both cultivars at the same time, we performed commercial-scale trials on 'Floridian' at the ca. 1 g fruitlet stage.…”
Section: Ejject Oj 245-tp On Th E Occurrence Oj Shrivelled Seedsmentioning
confidence: 99%
“…'Floridian' tends to have degenerate seeds after self-pollination and to produce a higher yield when located near 'Mauritius', whereas 'Mauritius' is self-fruitful (Stern et ai., 1993;Degani et al, 1995a). The significant increase in the percentage of fruit with shrivelled seeds following treatment with 2,4,S-TP (Table III) suggests that the pronounced late abscission of 'Floridian' fruitlets is intensified by seed degeneration as a consequence of inbreeding depression (Sedgley and Griffin, 1989).…”
Section: Ejject Oj 245-tp On Th E Occurrence Oj Shrivelled Seedsmentioning
confidence: 99%